Photon Absorption Models in Nanostructured Semiconductor Solar Cells and Devices - Luque, Antonio (Springer, 2016)
This book is intended to be used by materials and device physicists and also solar cells researchers. It models the performance characteristics of nanostructured solar cells and resolves the dynamics of transitions between several levels of these devices. An outstanding insight into the physical behaviour of these devices is provided, which complements experimental work. This therefore allows a better understanding of the results, enabling the development of new experiments and optimization of new devices. It is intended to be accessible to researchers, but also to provide engineering tools which are often only accessible to quantum physicists.